Nou aléz nan mizé: desenvolver o conceito “Fome Cultural” para compreender a fome na perspectiva haitiana - Exime, Ethol (2024)
This thesis research focuses on the chronic natural, social, and cultural calamities that afflict Haitian society, based on political, economic, and social crises. The thesis is made up of 6 papers, which were fundamental to the evolution of theoretical and empirical knowledge in the investigation of the problems that drove this research into hunger. Article 1 addresses the problem of hunger in Haiti as a scourge that can be combated through other understandings and studies of the roots of poverty. This is a qualitative study, the aim of which is to identify the main discussions about hunger and poverty in Haiti in scientific research that has already been carried out, to provide a basis for the concept of Cultural Hunger and to understand how these works are theorizing the subject of hunger in the Haitian context. This highlights the need to propose new ways of thinking about hunger in Haiti. Article 2 seeks to explain the connection between Haitian historical events and the political, economic, and social crises in that society and how external interference has been effective in shaping Haiti's history and society. With the support of August Ludwig (von) Schlözer's historical-critical method, the demand for accountability in public spending is emphasized to avoid corruption. Article 3 is guided by a single question: how are knowledgeable Haitian and non-Haitian researchers researching, thinking about, and analyzing Haitian hunger and poverty? This is a theoretical essay with bibliographic review aspects that analyzes 34 works, including theses, dissertations, articles, and reports published in French, English, Spanish and Portuguese on the subject, analyzed using the MAXQDA tool. There is a lack of innovative ideas on how to tackle hunger in Haiti. Article 4 is characterized by a qualitative case study in which the aim is to discuss the elements related to hunger and malnutrition in Haiti, associating them with issues such as the emergence of chronic diseases, the mortality rate, and constant climatic events in the country. It asks how governmental and non-governmental initiatives are contributing to improving the lives of Haitians in the fight against hunger. It highlights the continuing high rate of hunger and poverty, with 82% of the population still living in severe and moderate food insecurity in 2023, culminating in the discontinuation of any initiatives and projects, such as Ti Manman Cheri, Kore paysan, Kantin Mobil, PSUGO and Kantin Fix, against hunger. Article 5 stands out for its original theoretical construction of the conceptual proposal that hunger in Haiti is cultural. The aim is to develop the concept of Cultural Hunger theoretically and to understand the elements that condition its existence. The main constructive cultural elements of the Cultural Hunger concept are answered, using authors such as Frantz Rousseau Déus, Arturo Escobar, Pierre Daix, Demesvar Delorme, Jean-Jacques Rousseau, Jean Price-Mars; Amartya Sen and Boaventura de Sousa Santos, articulating sixteen elements. There is a lack of studies that have tried to construct a concept similar to the one proposed in this thesis. Finally, article 6 looks at the existence of the concept of Cultural Hunger from a Haitian perspective. Its aim is to identify and understand the calamitous elements of Haitian society that help to elucidate the construction of the concept of cultural hunger from the perceptions of Haitians. Guided by the question: how can we understand extreme hunger in Haiti and verify the existence of Cultural Hunger? This is an empirical study of 60 Haitian citizens in two cities, Marigot and Miragoâne, using content analysis followed by an ethnographic study as methodologies. The data was analyzed using Maxqda analytical software. Faced with the complexity of socio-cultural problems, hunger is not just a consequence of the vulnerabilities of the country's economic, political, and social issues. There is an urgent need for a change in mentality to break the cultural patterns of grandfathers, fathers and relatives that lead to the acceptance of hunger as something normal. The hypothesis confirms that hunger in Haiti is cultural. It is argued that Haiti's problems are chronic natural, social, and cultural calamities. The possibility of reducing hunger is advocated, with public policies that provide support for a change in mentality regarding the acceptance of "nou aléz nan mizé".